Exul Patriae. Claude Antoine Pochard (1766–1833) and His Exile in Poland—Tribulations of a Refractory Priest - Grzeszczak, Jan; Sukiennicka, Marta; Wilgosiewicz-Skutecka, Renata (Sensus Historiae, 2024)
The article focuses on the life of Claude Antoine Pochard, a prêtre réfractaire who was forced to leave France during the French Revolution and go into exile. After years of wandering across Europe, Pochard settled in Poland, where he took a position as the tutor to the sons of Józef Skórzewski, the starosta of Gniezno. He documented his experiences in memoirs, the unpublished manuscript of which is preserved in the University Library in Poznań and the Poznań State Archives. These four volumes, covering the years 1792–1833, provide a detailed account of Pochard’s life as an exile, his experiences in a foreign land, and how Poland eventually became his second homeland.